Advances in the Regulation of Macrophage Polarization by Mesenchymal Stem Cells and Implications for ALI/ARDS Treatment - Liu, Chang; Xiao, Kun; Xie, Lixin (Frontiers in Immunology, 2022)
Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a common condition with high mortality. ALI/ARDS is caused by multiple etiologies, and the main clinical manifestations are progressive dyspnea and intractable hypoxemia. Currently, supportive therapy is the main ALI/ARDS treatment, and there remains a lack of targeted and effective therapeutic strategies. Macrophages are important components of innate immunity. M1 macrophages are pro-inflammatory, while M2 macrophages are anti-inflammatory and promote tissue repair. Mesenchymal stem cells (MSCs) are stem cells with broad application prospects in tissue regeneration due to their multi-directional differentiation potential along with their anti-inflammatory and paracrine properties. MSCs can regulate the balance of M1/M2 macrophage polarization to improve the prognosis of ALI/ARDS. In this paper, we review the mechanisms by which MSCs regulate macrophage polarization and the signaling pathways associated with polarization. This review is expected to provide new targets for the treatment of ALI/ARDS.